Professional practice in times of pandemic covid-19: case cecar university corporation of the caribbean - Mendivil Hernandez, Patricia; Gonzalez Sanchez, Eduardo; Alvarez Ruiz, Liliana (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
The professional practice is the means that allows students to apply the knowledge learned during their training process and strengthen the competencies of knowing, knowing how to do and being/coexisting. The article synthesizes the characteristics and processes developed from the professional practice course at the Corporación Universitaria del Caribe in pandemic. Meanwhile, the practice process was adapted to the contingency by adopting new modalities of practice at institutional level (telepractice, work at home, advisor/tutor practice, research, entrepreneurship and telepsychology) to guarantee the students the pedagogical space that allowed them to put into practice their knowledge and disciplinary competences.